Challenges And Opportunites Of Female Journalists In Digital Industry Era - Mastanora, Refika; Maimori, Romi (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
The profession as journalists is identical with men since the war age. It is true because the heavy workload of journalist required physical ability, logical thinking, speed and strength in dealing with any situation. However, in this digital era, women are interested with journalism. The support systems around women are very necessary since the task of female journalist is not only about technical and theoretical abilities, but also about family income opportunity. This research aims to identify the challenges and opportunities of female journalists in the digital era. The results show that being female journalists are not easy as well as journalism. They need self-security in running their profession since they are vulnerable being victims of violence in the field; both physically and sexually. In addition, female journalists have job opportunities in contributing as reporters, news anchors, news editors, and so forth.